Synergistic Antihyperglycemic Effects of Soursop Leaves and Garlic in Alloxan-Induced Rats - Suswidiantoro, Vicko; Safutri, Wina; Pratiwi, Mida; Putri, Diah Karika; Dwiningrum, Riza; Lestari, Fina Aulika (PT FORMOSA CENDEKIA GLOBAL, 2024)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels due to impaired insulin production. Natural remedies, such as soursop leaves (Annona muricata) (SL) and garlic (Allium sativum) (GAR), are known for their antihyperglycemic properties. This study aimed to investigate the effects of SL and GAR extracts, individually and in combination, on reducing blood glucose levels in alloxan-induced diabetic rats. A total of 24 male Wistar rats were divided into six groups, receiving treatments of either metformin, SL, GAR, or their combination for seven days following alloxan administration to induce hyperglycemia. Blood glucose levels were measured before and after induction, and post-treatment on day 15. The results showed that the combined extracts exhibited better antihyperglycemic activity compared to individual treatments, with the most effective dose being 26.3 mg/kg BW SL + 31.5 mg/kg BW GAR.